9A.07: CARDIOVASCULAR TARGET ORGAN DAMAGE IN PREMENOPAUSAL SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS AND IN CONTROLS. ARE THERE ANY DIFFERENCES?. (June 2015) - Paini, A.; Andreoli, L.; Salvetti, M.; Dall'Ara, F.; Piantoni, S.; Donini, C.; Rosei, C. Agabiti; Bertacchini, F.; Stassaldi, D.; Rosei, E. Agabiti; Tincani, A.; Muiesan, M. L.
Abstract : Objective: In patients with systemic lupus erythematosus (SLE) a greater prevalence of structural and functional cardiovascular (CV) alterations has been described, possibly explaining the higher incidence of CV events, as compared to subjects matched for age and sex. Aim of this study was to analyze the presence of target organ damage in premenopausal women with SLE and in controls matched not only for demographic characteristics but also for other cardiovascular risk factors. Design and method: 34 patients with SLE clinically stable (SLEDAI Score 2.5 +/- 1.5) (mean age 32 ± 7 years, range 19–44) and 34 controls matched for sex, age, body mass index (BMI), clinic blood pressure (BP) and antihypertensive treatment (if present), underwent: 24 hours BP monitoring, echocardiography with tissue Doppler analysis (TDI) for the evaluation of left ventricular (LV) structure and of systolic and diastolic function, carotid ultrasound for intima-media thickness (IMT) and carotid distensibility measurement, and pulse wave velocity measurement for aortic stiffness (PWV). Results: By definition no difference was observed for age, sex, BMI and clinic BP values and a similar Framingham risk score was observed between SLE and controls (1.3 ± 2.7 vs 1.5 ± 2.3%, p = ns). No significant differences were observed for all echocardiographic parameters except LV longitudinal systolic function (Sm), an early index of LV systolic dysfunction (see Table). Carotid IMT and distensibility, as well as PWV and the prevalence of an abnormal aortic stiffness were both similar in the two groups. At the logistic analysis, PWV was independently associated with LV mass in controls and with the steroid weekly dose in SLE patients. Figure. No caption available. Conclusions: In patients with SLE and low activity index of the disease we did not observe significant vascular alterations as compared to controls with similar cardiovascular risk. The early LV systolic impairment observed in this group of patients needs confirmation in larger cohorts.